Determinants and Causes of Stillbirth in South Africa: Systematic Literature Reviewand Bibliometric Analysis - Simbarashe Magaisa; Dr. Nirmala Dorasamy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Stillbirth remains a significant public health challenge in South Africa, with complex determinants and causes contributing to its prevalence. This systematic literature review aims to identify and analyze the key determinants and causes of stillbirth in South Africa, utilizing VOSviewer for data visualization and bibliometric analysis. A comprehensive search was conducted across multiple academic databases, focusing on studies published between1994 and 2024. Studies were screened, evaluated, and selected based on predefined inclusion and exclusion criteria, focusing on maternal health, healthcare access, socio-economic conditions, and clinical care practices. The analysis revealed several critical determinants of stillbirth in South Africa, including poor antenatal care quality, maternal infections, hypertension, diabetes, preterm birth, and insufficient healthcare infrastructure, particularly in rural and under-resourced areas. Socio-economic factors, such as poverty, limited access to healthcare services, and cultural practices, also emerged as significant contributors. VOSviewer was employed to visualize co-occurrence networks, revealing relationships between these determinants and key research themes in the literature. The findings highlight the multifactorial nature of stillbirth in South Africa, emphasizing the need for comprehensiveevidence-based interventions targeting both clinical and socio-economic factors. Using VOSviewer allowed for a deeper understanding of the research landscape, identifying gaps in the existing literature and areas for future investigation. This review contributes to the ongoing efforts to reduce stillbirth rates in South Africa by providing evidence-based insights to inform public health policies and maternal healthcare practices specifically in low-income rural districts.